Healthcare use according to deprivation among French Alzheimer's Disease and Related Diseases subjects: a national cross-sectional descriptive study based on the FRA-DEM cohort - Couret, Anaïs; Lapeyre-Mestre, Maryse; Renoux, Axel; Gardette, Virginie (Frontiers in Public Health, 2024)
Introduction Pluriprofessional and coordinated healthcare use is recommended for Alzheimer's Disease and Related Diseases (ADRD). Despite a protective health system, France is characterized by persistent and significant social inequalities in health. Although social health inequalities are well documented, less is known about social disparities in healthcare use in ADRD, especially in France. Therefore, this study aimed to describe healthcare use according to socioeconomic deprivation among ADRD subjects and the possible potentiating role of deprivation by age. Methods We studied subjects identified with incident ADRD in 2017 in the French health insurance database (SNDS). We described a large extent of their healthcare use during the year following their ADRD identification. Deprivation was assessed through French deprivation index (Fdep), measured at the municipality level, and categorized into quintiles. We compared healthcare use according to the Fdep quintiles through chi-square tests. We stratified the description of certain healthcare uses by age groups (40–64 years, 65–74 years, 75–84 years, 85 years, and older), number of comorbidities (0, 1, 2–3, 4 comorbidities and more), or the presence of psychiatric comorbidity. Results In total, 124,441 subjects were included. The most deprived subjects had less use of physiotherapy (28.56% vs. 38.24%), ambulatory specialists (27.24% vs. 34.07%), ambulatory speech therapy (6.35% vs. 16.64%), preventive consultations (62.34% vs. 69.65%), and were less institutionalized (28.09% vs. 31.33%) than the less deprived ones. Conversely, they were more exposed to antipsychotics (11.16% vs. 8.43%), benzodiazepines (24.34% vs. 19.07%), hospital emergency care (63.84% vs. 57.57%), and potentially avoidable hospitalizations (12.04% vs. 10.95%) than the less deprived ones. Discussion and conclusion The healthcare use of subjects with ADRD in France differed according to the deprivation index, suggesting potential health renunciation as in other diseases. These social inequalities may be driven by financial barriers and lower education levels, which contribute to health literacy (especially for preventive care). Further studies may explore them.